Nanomaterials and security in occupational and forensic medicine: insights from nanotoxicology - Tran, Lang; Treglia, Michele; Coppeta, Luca; Ferrari, Cristiana; Pallocci, Margherita; Campagnolo, Luisa; De Miranda Junior, Luiz C.; Piccoli, Bruno; Gaskin, Sharyn; Cortes Fernandes, Francisco; Dantas Filho, Fabio; Passalacqua, Pierluigi; et al. (Frontiers in Toxicology, 2024)
Nanoenergetics are defined as a class of nanomaterials that possess the ability to release energy in certain situations. These properties have been studied and deepened in recent years, so much so that nanoenergetics have been introduced into the use of the weapons industry, among others. It is therefore an emerging reality that deserves attention with regard to potential harmful effects on human and environmental health. it has been suggested that nanoenergetics may have genotoxic and immunotoxic effects, among others. Problems related to exposure to nanonenergetics can therefore potentially affect both exposed workers (both in the production and use phase) and the civilian population, if used in war scenarios, for example,. Starting from these assumptions, the INNOTOX research project aims to contribute to the in-depth study of the toxicity of nanonenergetics, through an integrated approach involving experts in occupational and forensic medicine, nanotoxicology and bioengineering.